Analisis Gaya Mengajar Guru Kelas Tinggi pada Pembelajaran Menulis Narasi di Kecamatan Wado - Noviana Budianty; Rahman Rahman; Vismaia Sabariah Damaianti (Jurnal Administrasi Pendidikan, 2022)
This study aims to analyze and determine the teaching style used by upper-class teachers in learning to write narratives in, with the respondents were teachers in 13 schools in the sub-district Wado District. The research approach used is a qualitative through descriptive methods with the type of research survey research, by distributing questionnaires through google form, then the data was analyzed by reduction and resentation data, and drawing conclusions. There are seven indicators that are used as a reference to see the sequence of learning carried out by the teacher. The results of the study were dominant teaching style used by 77.40% the teacher in learning to write narratives is an interactional teaching style. 84.6% of the application was mostly carried out by teachers was guiding students in determining themes, topics, and messages to be conveyed. Meanwhile, the lowest indicator is for determining the audience with around 30.7. To analyze the teacher's teaching style, it has transformed to 15 questions from all indicators of the teacher's teaching style. After collecting data, it was concluded that at the implementation stage of learning to write narratives, not all teachers applied these indicators.